2018
DOI: 10.1111/jtxs.12350
|View full text |Cite
|
Sign up to set email alerts
|

Effects of breed‐production system on collagen, textural, and sensory traits of 10 European beef cattle breeds

Abstract: To differentiate a product in the market, it is necessary to define its characteristics. Differentiation allows increasing the added value of products and, therefore, income of the farmers. In addition, it guarantees to the consumers that the product they purchase has the intrinsic and extrinsic quality features that they seek. For consumers, beef texture is one of the most important quality attributes sought, therefore, studying factors that can affect beef texture is a major interest for the industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 48 publications
0
10
2
2
Order By: Relevance
“…However, they pointed out that meat from Angus and Limousin steers was judged by panelists significantly more tender than that of the Simmental steers, meanwhile Charolais meat was scored intermediate. Our finding does not support the previous research of Panea et al [13], who have carried out a thorough analysis of ten European cattle breeds, resulting that AV and RE were similar in tenderness. These differences could be attributed to variations in the feeding system (Intensive), ageing time (14 days), and possible variations during the thawing and cooking process (time and/or temperature), as indicated Lepetit et al [46], who evaluated the effect of cooking temperature/time in compression stress of several muscles in the range 20-80 • C. In our work, the effect of livestock production system and pre-slaughter handling on this parameter should be analyzed within each breed due to the interactions.…”
Section: Effect Of Breed Livestock Production and Pre-slaughter Hancontrasting
confidence: 99%
See 1 more Smart Citation
“…However, they pointed out that meat from Angus and Limousin steers was judged by panelists significantly more tender than that of the Simmental steers, meanwhile Charolais meat was scored intermediate. Our finding does not support the previous research of Panea et al [13], who have carried out a thorough analysis of ten European cattle breeds, resulting that AV and RE were similar in tenderness. These differences could be attributed to variations in the feeding system (Intensive), ageing time (14 days), and possible variations during the thawing and cooking process (time and/or temperature), as indicated Lepetit et al [46], who evaluated the effect of cooking temperature/time in compression stress of several muscles in the range 20-80 • C. In our work, the effect of livestock production system and pre-slaughter handling on this parameter should be analyzed within each breed due to the interactions.…”
Section: Effect Of Breed Livestock Production and Pre-slaughter Hancontrasting
confidence: 99%
“…According to phylogenetic studies [3,4] the Spanish cattle breeds encompass two main groups: one group includes the RE and the other one contains the RG, while AV occupies an intermediate position. Carcass and meat quality from these breeds have been widely studied under different production systems [5][6][7][8][9][10][11][12] However, there are few papers which compare these breeds in terms of meat quality traits, and little is available on sensory and flavor characteristics of these three breeds, with two exceptions [8,13].…”
Section: Introductionmentioning
confidence: 99%
“…At T 0 , the highest WB parameters values were observed, and in both shear force and total work, values reduced from T 0 to T 14 , although after 14 days of ageing, no changes were observed in these parameters. In the present study, shear force values at 14 days of ageing were higher than those reported by other authors [ 51 , 68 ] for conventional meat from the Retinta breed.…”
Section: Resultscontrasting
confidence: 88%
“…A lack of correlation between Warner-Bratzler and compression test (TPA) parameters is usually found [ 68 ], as noted in this study. In this sense, our results only indicated a positive correlation between shear force and chewiness (0.393; p ≤ 0.01).…”
Section: Resultsmentioning
confidence: 64%
“…Y una segunda vertiente derivada de los cambios directos en el manejo y en las prácticas ganaderas de diversas especies. Varios estudios sobre la calidad de la carne reflejan como el sistema de producción origina modificaciones tanto en la calidad físicoquímica como organoléptica del producto, así como existen variaciones dependiendo de las propias razas (Koutsidis et al, 2008;Christensen et al, 2011;Panea et al, 2018).…”
Section: Crisis Climática: Su Impacto Sobre La Producción Animalunclassified